Socialization of the Use of Healthy Social Media to Anticipate Cyberbullying at the Situ Rompong Reading Park - Aryanto, Aryanto; Priscilia, Amanda; Suryadi, Fifian Eka; Muttaqin, Muhamad Luthfi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This activity aims to increase children's understanding of the dangers of cyberbullying through outreach at the Siturompong Reading Park. The methods used include interactive socialization, case studies, and educational games to create a learning atmosphere that is fun and easy to understand. The results show an increase in children's understanding of the negative impacts of cyberbullying and how to recognize and prevent it. This activity succeeded in building digital literacy in children and strengthening the role of reading parks as community-based education centers.